2012
DOI: 10.3354/meps09435
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure, coloration, and morphometrics of yellowhead jawfish Opistognathus aurifrons (Perciformes: Opistognathidae) in the Caribbean region

Abstract: We investigated intraspecific variability in phenotype and population genetic structure of yellowhead jawfish Opistognathus aurifrons from 4 different locations in the Caribbean region: South Florida (USA), Bimini (Bahamas), St. Thomas (US Virgin Islands), and Aruba. Discriminant function analysis (DFA) of 9 melanistic traits in the head region resulted in clear separation between Bimini and the other 3 populations. South Florida, St. Thomas, and Aruba slightly overlapped in patterning, with St. Thomas forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…In addition, Chrysoblephus laticeps showed haplotype diversity of 1 for all sites studied, but with overall haplotype diversity not equal to 1 (Teske et al 2010), and Naso vlamingii was observed to have haplotype diversity of 1 even with a large sample size (n ¼ 113) (Klanten et al 2007). Moreover, equal number of samples and haplotypes was also observed in Opistognathus aurifrons using concatenated sequence of mtDNA CR and cytochrome oxidase I (Ho et al 2012). These suggest that the diversity represented by the samples in our study might not be low, but reflects the high genetic diversity typical of many marine fishes (Grant and Bowen 1998).…”
Section: Discussionsupporting
confidence: 52%
“…In addition, Chrysoblephus laticeps showed haplotype diversity of 1 for all sites studied, but with overall haplotype diversity not equal to 1 (Teske et al 2010), and Naso vlamingii was observed to have haplotype diversity of 1 even with a large sample size (n ¼ 113) (Klanten et al 2007). Moreover, equal number of samples and haplotypes was also observed in Opistognathus aurifrons using concatenated sequence of mtDNA CR and cytochrome oxidase I (Ho et al 2012). These suggest that the diversity represented by the samples in our study might not be low, but reflects the high genetic diversity typical of many marine fishes (Grant and Bowen 1998).…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies of several populations of Caribbean O.aurifrons based on morphology (Böhlke and Thomas 1961) and genetics (Ho et al 2012) indicated that despite substantial variation in color pattern within and between populations, only a single species should be recognized. Several other western Atlantic reef fishes, especially small, cryptobenthic fishes like gobies and blennioids, show similar patterns where there is substantial mitochondrial divergence without detectable phenotypic differences (Victor et al 2015; Victor 2015).…”
Section: Phylogenetic Relationships Of Western Atlantic Opistognathusmentioning
confidence: 99%
“…Frédérich et al 2012), mainly focusing on the association between coloration polymorphism and genetic differentiation (Schultz et al 2007). While some of these studies have found geographic concordance between morphologic and genetic data (Drew et al 2010) others have uncovered discordance between the measured morphological and genetic traits (Ho et al 2012). Similarly, several investigations on marine fishes have assessed the relationships between morphology and environmental factors; however, studies examining the relative contribution of environmental and genetic variation on morphology across natural populations are scarce (but see Marcil et al 2006;Costa et al 2010), and to our knowledge are lacking for coral reef fishes.…”
Section: Introductionmentioning
confidence: 97%